Dimensi Tawasul dalam Tafsir Al-Qur’an: Dialog Sufistik dan Teologis dalam Memahami Ayat-ayat Wasilah - Nurmayanti, Lutfiya; Rofi'i, Muhammad Arwani (Universitas Islam Negeri Madura, 2025)
The issue of tawasul is often a point of debate among the public, both lay and learned. This difference is mainly related to tawasul through the glory of someone, both living and deceased, including tawasul to the Prophet Muhammad saw.. In the Islamic tradition , not all forms of tawasul are allowed. The Qur'an discusses the concept of tawasul in Surah Al-Maidah (5): 35 and Al-Isra' (17): 57, which is then interpreted variously by the mufasirs. This study aims to examine the dimension of tawasul in the interpretation of the Qur'an through a comparative analysis of two different styles of interpretation, namely Sufistic interpretation (Laṭā’if al-Isyārāt by al-Qusyairĭ) and theological interpretation (al-Tafsīr al-Kabīr by Ibn Taymiyyah). The research method used is library research with descriptive and comparative approaches. The researcher describes the interpretation of the two mufasirs on the verses of tawasul, then compares the similarities and differences in their approach to the concept of wasilah. The results show that al-Qusyairĭ and Ibn Taymiyyah have an understanding in permitting tawasul through good deeds and faith in Allah and His Messenger. However, there are fundamental differences in their approach to tawasul through the intermediary of creatures. Al-Qusyairĭ in Laṭā’if al-Isyārāt emphasizes that tawasul encompasses a broader spiritual dimension, where intermediaries such as the Prophet and the saints can be a means of getting closer to Allah, as long as they maintain sincerity and faith in worship. Meanwhile, Ibn Taymiyyah in al-Tafsīr al-Kabīr rejects any form of tawasul that involves humans as intermediaries, asserting that the legitimate approach to tawasul is through direct prayer to Allah, without intermediaries other than faith and good deeds.